Adição da α-amilase em dietas com redução de energia metabolizável para suínos - Rupolo, Paulo Evaristo (2022)
A study was conducted to assess the effect of adding α-amylase in diets with or without reduced metabolizable energy (ME) for growing-finishing pigs on the apparent total tract digestibility of nutrients and apparent energy (ADTT), nitrogen balance, zootechnical performance, blood metabolites and carcass and meat attributes. In Expt. I, 36 entire male piglets (25.9 ± 0.5 kg BW) were allocated to a randomized block design (RBD), with 4 treatments: (1) control diet (CD) without α-amylase and without reduction of ME, (2) CD + 100 g of α-amylase/t and without reduction of ME (AM0), (3) CD + 100 g of α-amylase/t with reduction of 50 kcal ME/kg (AM-50) and (4) CD + 100 g α-amylase/t with reduction of 100 kcal of ME/kg (AM-100), and 9 repetitions. The DATT (ADCTT) coefficients of gross energy (GE) and of GE metabolizability were higher (P < 0.05) in pigs fed α-amylase compared to CD. Ext. II answered entire male piglets 42 pigs (25.8 ± 0.2 kg BW) allocated to a RBD, with 6 treatments: (1) CD, (2) CD without α-amylase with 50 kcal ME reduction (CD-50), (3) CD without α-amylase with reduction of 100 kcal of ME/kg (CD-100), (4) CD + 100 g of αamylase/t and without reduction of ME (AM0), (5) CD + 100 g of α-amylase/t with a reduction of 50 kcal of ME/kg (AM-50) and (6) CD + 100 g of α-amylase/t with a reduction of 100 kcal of ME/kg (AM-100), and 7 repetitions. The growing pigs I in the AM group had (P < 0.05) higher feed-to-gain ratio compared to CD, differing from the results in termination phase I. weight compared to those fed with AM. The growing pigs in the AM group had (P < 0.05) higher DP compared to CD, and higher (P < 0.10) ADCTTMS, DDM, DOM and DE than the CD group in the finishing phase. Animals from the concentrated AM group, the smallest (P < 0.5) of higher protein depth and lower a* value protein fed mineral meat compared to those fed meat with CD. In conclusion, α-amylase alone to a single definition and sustaining the performance in those fed diets compared to ME, without definition of set as other variables.